(untitled) (International journal of medical sciences, 2026)
The clinical and functional changes induced by these diseases commonly manifest as pain, discomfort, bleeding on probing, swelling, ulceration, diminished masticatory efficiency, altered speech, and aesthetic concerns. Such outcomes not only impact oral functions but also have significant psychological and social ramifications for affected individuals, potentially leading to reduced self-esteem and impaired quality of life. Thus, the management of oral diseases in pubertal girls should be holistic, addressing not only the biological aspects but also the psychological and social dimensions of health.